Pengaruh Pupuk Organik Cair Limbah Tahu terhadap Pertumbuhan dan Produksi Jagung Pulut (Zea mays Ceratina) - Galushasti, Andarula; Rahmawati, Hidayatul; Soelaksini, Liliek Dwi; Utami, Christa Dyah (Program Studi Agroteknologi INSTIPER, 2024)
Corn is one of the food crops in Indonesia that has great potential to be developed, one of which is Waxy Corn. This type of corn has a high amylopectin content, but its productivity is still relatively low. One effort to increase the productivity of Waxy Corn is through the use of liquid organic fertilizer from tofu waste. This research was conducted on the land of the Jember State Polytechnic in July-October 2024 using a randomized block design with a single treatment, namely the comparison of the concentration of liquid organic fertilizer tofu waste. There are six treatment levels, namely control (0 ml/l), 26 ml/l, 28 ml/l, 30 ml/l, 32 ml/l, and 34 ml/l. The data were analyzed using analysis of variance, and if there was a significant difference, a further test of the smallest significant difference was carried out. The results showed that the treatment of liquid organic fertilizer with a concentration of 34 ml/l had a significant effect on the stem diameter at the age of 21 days after planting and the weight of the cob per sample. The concentration of 30 ml/l affected the cob diameter, while the concentration of 32 ml/l affected the cob weight per plot. The parameters of plant height and biomass weight did not show significant differences.